PERMODELAN TRANSPORT LINDI DENGAN KONTAMINAN Pb DAN Mn MENGGUNAKAN SOFTWARE POLLUTE.v7 (STUDI KASUS TPA NGRONGGO, KOTA SALATIGA) - Evelyne Hanaseta; Badrus Zaman; Mochtar Hadiwidodo (Jurnal Teknik Lingkungan, 2013)
Leachate concentration for Pb and Mn parameters from TPA Ngronggo, Salatiga  are exceed equal to Perda Jateng No. 5/ 2012, consentration of this parameters are  0,75 mg/l and 14,1 mg/l. Contamination of heavy metals are spreads from water soil current to landfill region. This landfill used controlled landfill method. Formation of lining system are gravel, geotextile, geomembrane, compacted clay, and soil. The result from monitoring well are suspicion because of transport contaminant from landfill are attain to 7,1m of depth. Simulation of this phenomena can use Pollutev.7 software, we can see 1,5 dimensional of the result. Prediction consentration for 15 years are Pb 0,6728 and Mn 12,5 mg/l.